Two human menopausal gonadotrophin (hMG) preparations display different early signaling in vitro. (21st October 2020) - Casarini, Livio; Riccetti, Laura; Paradiso, Elia; Benevelli, Riccardo; Lazzaretti, Clara; Sperduti, Samantha; Melli, Beatrice; Tagliavini, Simonetta; Varani, Manuela; Trenti, Tommaso; Morini, Daria; Falbo, Angela; et al.
Abstract: Commercial hMG drugs are marketed for the treatment of infertility and consist of highly purified hormones acting on receptors expressed in target gonadal cells. Menopur ® and Meriofert ® are combined preparation of FSH and hCG and are compared in vitro herein. To this purpose, the molecular composition of the two drugs was analyzed by immunoassay. The formation of FSH receptor and LH/hCG receptor (FSHR; LHCGR) heteromer, intracellular Ca 2+ and cAMP activation, β-arrestin 2 recruitment and the synthesis of progesterone and estradiol were evaluated in transfected HEK293 and human primary granulosa lutein cells treated by drugs administered within the pg-mg/ml concentration range. Molecular characterization revealed that Meriofert ® has a higher FSH:hCG ratio than Menopur ® which, in turn, displays the presence of LH molecules. While both drugs induced similar FSHR-LHCGR heteromeric formations and intracellular Ca 2+ increase, Meriofert ® had a higher potency than Menopur ® in inducing a cAMP increase. Moreover, Meriofert ® revealed a higher potency than Menopur ® in recruiting β-arrestin 2, likely due to different FSH content modulating the tridimensional structure of FSHR-LHCGR-β-arrestin 2 complexes, as evidenced by a decrease in bioluminescence resonance energy transfer signal. This drug-specific activation of intracellular signaling pathways is consistent with the molecular composition of these preparations and impacts downstream progesterone and estradiol production, with Menopur ® more potent than Meriofert ® in inducing the synthesis of both the steroids. These findings are suggestive of distinct in-vivo activities of these preparations, but require cautious interpretation and further validation from clinical studies.